The Determinants of International Portfolio Holdings and Home Bias - Li, Shujing (IMF Working Papers; Working Paper, 2004)
Despite the liberalization of foreign portfolio investment around the globe since the early 1980s, the home-bias phenomenon is still found to exist. Using a relatively new IMF survey dataset of cross-border equity holdings, this paper tests new structural equations from a consumption-based asset-pricing model on international portfolio holdings. Using of stock data allows us to provide new and clear-cut evidence on the determinants of international portfolio holdings.